ANALISIS PROKSIMAT DAN UJI ORGANOLEPTIK BERAS ARTIFISIAL BERBAHAN DASAR TEPUNG SINGKONG (Manihot esculenta Crantz) dan TEPUNG KACANG MERAH (Phaseolus vulgaris L.) DENGAN PERBANDINGAN FORMULASI YANG BEBEDA - S Salimna; Munifatul Izzati; Sri Haryanti (Jurnal Akademika Biologi, 2014)
Artificial rice is rice made from non-carbohydrate rice approached or exceeded conventional rice. Making artificial rice from cassava flour and kidney bean flour is solution for the needs of healthy food society . This experiment aims to analyze and assess the nutritional value of artificial rice made from cassava flour and kidney bean by means of proximate analysis and to analyze and assess the preference level for artificial rice. Experimental studies using a Completely Randomized Design (CRD) with one factor, namely the number of comparisons cassava flour to kidney bean flour, consisted of 3 standard formula is  F1 with comparison between cassava and kidney bean flour as much 2:1, F2 with comparison between cassava and kidney bean flour as much 1:1 and F3 with comparison between cassava and kidney bean flour as much 1:2. The methods of this experiment were proximate analysis and test preferences value. The results show that the formula of  artifisial rice that the best nutrition has formula with a ratio of cassava flour and kidney bean was F3 with comparison between cassava and kidney bean flour as much 1:2. Formula F3 has ash content of 3,8%; water content 9,2%; crude fiber content of 7,4%; 8% protein; carbohydrate content 78,5% and antioxidant levels 21,6%. Test the preferences value show that the artificial rice made from cassava and kidney bean flour formula is F1 with comparison between cassava and kidney bean flour as much 2:1, followed of F3 with comparison between cassava and kidney bean flour as much  1:2 and F2 with comparison between cassava and kidney bean flour as much 1:1.Keywords: artifisial rice, proximate analysis, preferences value